Educational Transformation: Using Virtual Reality as a Learning Tool for The Future - Akbar, Jakub Saddam; Djakariah, Djakariah (Edutech Publishing Media, 2024)
Education continues to transform with the introduction of advanced technology such as Virtual Reality (VR). The use of VR as a future learning tool promises to revolutionize the way students learn and interact with course material. This research aims to explore the potential of VR to increase student engagement through a more interactive and immersive learning experience. The research method used is literature study. Through a literature study and analysis of recent developments, we see how VR can aid the understanding of complex concepts, such as science and mathematics, as well as improve understanding of historical content through realistic simulations. However, challenges such as device costs and curriculum integration need to be overcome to realize the full potential of this technology in education. It can be concluded that with the right strategy, VR can be the key to creating more personalized and effective learning experiences, leading to major transformations in the global education system. This research contributes to a more personalized and effective learning experience, which in turn can improve the quality of education and student learning outcomes